Patient Positioning System in Hospital Based on Zigbee - Chai Jihong (2011 International Conference on Intelligent Computation and Bio-Medical Instrumentation, 2011)
To facilitate the tracking and managing of patient in the hospital, wireless positioning network is constructed with the mesh topology by using the Zigbee protocol stack. The strongest base station positioning method is implemented by comparing the signal strength of the receiving data packets which is called RSSI. The hospital positioning system developed on the platform of MG2455 module achieves the function of patient positioning and emergency call, which could accurately get the patient ID and his location, and send to the central monitoring server to display the real time patient information. The wireless position system is not only easily installed and applied, but also has the feature of low power and high reliability.